Participatory Culture: A Study On Bangtan Boys Fandom Indonesia - Cendera Rizky Bangun (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2019)
In the past few years, South Korean pop culture has become a global phenomenon. The sudden popularity of the culture commonly known as as Korean Wave or Hallyu. This trend includes Korean drama, dance, music, films, animation, games, and fans club for Korean pop celebrity. In the past, those who become fans is only from a spesific age, but now it is more varied. One of most popular of the Korean singer groups is BangTan Boys. Abbreviated as BTS, the fans of BangTan Boys is proudly call themselves, â€œARMYâ€. Using the Henry Jenkinsâ€™s Participatory culture theory along with qualitative method, this research tries to analyze that there are audiens who do not only consuming pop culture, but also producing new cultural artefacts from that. The data were collected by focus group discussion, in-depth interview and data analysis. It shows that some of the fans are making â€œfanfictionâ€ as the reproductions of new artefacts, despite actively participating in BTS fandom by doing activities as include in the four types of Jenkinâ€™s participatory cultures.